Ecological restoration of eroded karst utilizing pioneer moss and vascular plant species with selection based on vegetation diversity and underlying soil chemistry. Issue 14 (6th December 2018) - Shen, J. C.; Zhang, Z. H.; Liu, R.; Wang, Z. H.
Abstract: Soil erosion in karst areas not only destroys the natural environment but also accelerates the decline in land productivity together with the associated increase in poverty for local communities. There are no simple or straightforward answers to controlling soil erosion on karst. Such erosion has become a serious problem in China. This study addresses both the diversity of vegetation (mosses, herbs, shrubs and trees) on karst and the underlying soil chemical characteristics, in order to provide a scientific basis by which suitable plant species can be selected for recovery and restoration of karst degraded by soil erosion. Vegetation diversity and soil chemistry were assessed in areas with five different grades of soil erosion in Guiyang Karst Park, Guizhou, China. Mosses are more tolerant than vascular plants of soil erosion and associated environmental degradation of karst and the order of species diversity was: mosses > herbs > shrubs > trees. Mosses were found to play a major role in ecological restoration of microhabitats on karst. Soil microbial biomass carbon was found to be significantly higher in soil under mosses than in bare soil associated with other plant categories. Mosses were more effective in converting unavailable potassium to available potassium. Vascular plants were found to have a positive effect on total nitrogen fixation and the availability of phosphorus in the soil. Increasing soil degradation was associated with lower levels of total Nitrogen in soil underlying mosses than in soil underlying vascular plants. Thus, based on their different but complementary contributions to soil chemistry, mosses and vascular plants in combination can provide the most practical outcome for the repair and restoration of areas of karst affected by soil erosion. The combination of the moss species, Homomallium plagiangium, Cyrto-hypnum pygmaeuman and Brachythecium perminusculum, the herbs Veronica arvensis and Youngia japonica, and the tree Prunus salicina, are recommended as suitable pioneer plant species to cultivate for use in restoration of regions of karstic soil erosion.